(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article deals with issues related to the government control by the lower chambers of the world’s parliaments, including the Legislative Chamber of the Oliy Majlis of the United States, France, Germany and the Republic of Uzbekistan, as well as improving the parliamentary institution oversight to transform our national parliament into a true school of democracy, establishment of effective cooperation mechanisms of lower house deputies of parliament with the deputy corps of local Councils.